THE INFLUENCE OF METHOD STORAGE ON FUNCTIONAL PARAMETERS OF POLLEN OF TABLE BEET - E. G. Kozar; S. A. Vetrova; M. I. Fedorova (Овощи России, 2018)
When working with pollen, it is important to keep its functional parameters for some time. To do this, you need to choose the best conditions to preserve pollen germination. The influence of different method of pollen storage of inbred plants of beetroot on its functional characteristics, at germination on artificial nutrient medium under conditions in vitro. When storing pollen in eppendorf tube for the second-third day, the pollen germination decreased by 3-10 times compared to the initial value, after a week of storage, pollen was in conglomerates, a lot of burst pollen. When stored on the sprigs for the seventh to eighth days, the decrease in pollen germination was no more than 30% of the control, and the growth rate of the pollen tube in most samples remained approximately at the control level. For a comparative analysis of the germination of pollen of inbred plants beetroot when evaluating a large set of samples, it is recommended to store flowering twigs in paper bags at a reduced temperature (10-12°C). This is important when working with a large set of samples where it is not possible to compare them at the same time.